Advanced Functional Nanostructures based on Magnetic Iron Oxide Nanomaterials for Water Remediation: A Review. (15th February 2021) - Leonel, Alice G.; Mansur, Alexandra A.P.; Mansur, Herman S.
Highlights: Nanotechnology offers choices to develop next generation of water treatment systems. Magnetic nanomaterials are encouraging options to traditional water treatment methods. Functionalization of iron oxide nanostructures for wastewater treatment is discussed. Benefits and limitations of MIONs for water remediation and research are highlighted. Opportunities for industrial wastewater treatment with nanomaterials are discussed. Abstract: The fast growth of industrialization combined with the increasing population has led to an unparalleled demand for providing water in a safe, reliable, and cost-effective way, which has become one of the biggest challenges of the twenty-first century faced by global society. The application of nanotechnology in water treatment and pollution cleanup is a promising alternative in order to overcome the current limitations. In particular, the application of magnetic iron oxide nanoparticles (MIONs) for environmental remediation has currently received remarkable attention due to its unique combination of physicochemical and magnetic properties. Given the broadening use of these functional engineered nanomaterials, there is a growing concern about the adverse effects upon exposure of products and by-products to the environment. This makes vitally relevant the development of green chemistry in the synthesis processes combined with a trustworthy risk assessment of the nanotoxicity of MIONs as the scientific knowledge of the potential hazard of nanomaterials remains limited. This work provides comprehensive coverage of the recent progress on designing and developing iron oxide-based nanomaterials through a green synthesis strategy, including the use of benign solvents and ligands. Despite the limitations of nanotoxicity and environmental risks of iron oxide-based nanoparticles for the ecosystem, this critical review presents a contribution to the emerging knowledge concerning the theoretical and experimental studies on the toxicity of MIONs. Potential improvement of applications of advanced iron oxide-based hybrid nanostructures in water treatment and pollution control is also addressed in this review. Graphical Abstract: Advanced magnetic iron oxide nanostructures: Powerful weapons for water research, treatment, and remediation. Image, graphical abstract